Rancang Bangun Aplikasi Administrasi Pendaftaran Pasien RSUD DR.SOEWANDHIE Surabaya - Darusman, Andi; Hariadi, Bambang; Shintawati, Rahayu Arya (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2018)
Hospitals Dr. Soewandhie is one hospitals in surabaya solid ongoing business processes in terms of service and examination of patients outpatient. Obstacles faced Hospitals Dr. Soewandhie is in data processing associated with the patient, the problem in the search data, which resulting in the case of duplication of medical card patients. Another obstacle is data inconsistency, recording data on the number patient visits different registration with the data on the amount of traffic check unit, manual data transfer and reporting process requires extra effort because scopied repeatedly prior to the general ledger. To overcome the above problems it created Design Patient Administration Systems in Hospitals Dr. Soewandhie, which can assist the administration in the registration section and check the unit that includes patient search, validation of patient, patient registration, patient queues, checks patients, drug registration and reporting. With the Design of the Patient Administration System Hospitals Dr. Soewandhie, it can provide more accurate information and assist in the search for patient data, prevent duplication of medical card, provide data on the number of patients that are consistent between the units, helping recording medical records and helps recording of dispensing. By processing the exact data it can produce useful information for the reporting head hospital.